Constructing the political spectacle - Edelman, Murray J. (Chicago University of Chicago Press, 1988)
Thanks to the ready availability of political news today, informed citizens can protect and promote their own interests and the public interest more effectively. Or can they? Murray Edelman argues against this conventional interpretation of politics, one that takes for granted that we live in a world of facts and that people react rationally to the facts they know. In doing so, he explores in detail the ways in which the conspicuous aspects of the political scene are interpretations that systematically buttress established inequalities and interpretations already dominant political ideologies.
Includes bibliographical references and index.
Keywords: Political psychology